2013
DOI: 10.7567/jjap.52.11nd01
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Effective Production of Very High Frequency Hydrogen Plasma Using a Balanced Power Feeding Method

Abstract: The characteristics of a VHF hydrogen plasma produced by a balanced power feeding method were examined by using a two-dimensional Monte Carlo fluid hybrid model. The simulation results showed that the electron density is maximum at a certain pressure between the discharge electrodes and significantly decreases outside the electrodes at a high gas pressure. The power absorption efficiency between the electrodes was improved by increasing the gas pressure. In addition, the plasma was produced efficiently between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…4(a), T e is uniform (∼2 eV) except around the discharge electrodes (T e = 5.5 eV), which is a typical characteristic of the CCP. [21][22][23][24] Figure 4(b) exhibits that V s is uniform between the discharge electrodes and an ambipolar field is formed outside them. Note that T e = 1.8 eV and V s = 34.2 V at y = 15 mm (near the substrate).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4(a), T e is uniform (∼2 eV) except around the discharge electrodes (T e = 5.5 eV), which is a typical characteristic of the CCP. [21][22][23][24] Figure 4(b) exhibits that V s is uniform between the discharge electrodes and an ambipolar field is formed outside them. Note that T e = 1.8 eV and V s = 34.2 V at y = 15 mm (near the substrate).…”
Section: Resultsmentioning
confidence: 99%
“…PHM is described in detail in Ref. 21. For a more strict simulation, the electron energy distribution function (EEDF) should be included.…”
Section: Description Of Simulation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we have simulated a BPF hydrogen plasma in a cylindrical chamber where the calculation area outside the electrodes is very large compared with that inside the electrodes. 21,22) It was confirmed that the BPF method reduced the electron density outside the electrodes and increased that inside the electrodes. In addition, we found that the discharge outside the electrodes decreased with high pressure in the BPF model.…”
Section: Introductionmentioning
confidence: 87%